Innovation in Marketing: The Emergence of New Technologies Shaping Future Marketing Concepts and Perspectives - Majid, M. Majid; Rajiman, Rajiman; Nugraheni , Evy Nahdia Zuliastuti; Busono, Aulia (Green Publisher Indonesia, 2025)
Rapid technological advancements have significantly impacted various fields, including marketing. This article examines the emergence of new technologies in the marketing industry and their influence on companies' strategies. The aim of this research is to develop a framework that understands the role and benefits of new technologies in shaping the future of marketing. In this study, researchers investigated various technologies that are on the rise in marketing, such as artificial intelligence, advanced data analytics, location-based marketing, and the application of blockchain technology in marketing campaigns. The researchers analyzed how these technologies have helped companies improve efficiency, target audiences more precisely, and create more personalized customer experiences. In addition, this article also discusses the challenges faced by companies in adopting and integrating new technologies in their marketing strategies. Technological advancements often bring new complexities and paradigm shifts, which can affect the way companies interact with consumers and the market as a whole. Therefore, the researcher proposes a framework that can help companies in understanding and addressing these challenges more effectively. The results of this research show that new technologies have opened up new opportunities in marketing, increased campaign creativity, optimized data management, and expanded brand reach globally. However, to take full advantage of the potential of this technology, companies must understand market shifts, consumer behavior, and industry trends. This article also explores how technology will further transform marketing, urging businesses to proactively adapt and integrate innovations.